Manajemen Mutu Pembelajaran, dari Pengaruh Kepemimpinan Kepala Sekolah, Kompetensi dan Motivasi Mengajar SMP di Kecamatan Lamaknen, Nusa Tenggara Timur - Asa, Yustrivat; Purbonuswanto, Welius; Darmowiyono, Mulyanto (Universitas Sebelas Maret, 2020)
This study uses a quantitative approach. The population in this study were all juniorhigh school teachers in the sub-district of Lamaknen, East Nusa Tenggara, totaling 75 people. The sample in this study used the total sampling method, meaning that the total population was 75 people. Data collection is done through the distribution of questionnaires that have been tested and have met the validity and reliability tests. Analysis of the data used include: descriptive analysis, multiple linear regression analysis and partial correlation analysis. Based on the results of the data analysis, conclusions are drawn: (1) There is a positive andsignificant influence of the Principal's leadership, teacher competence and teacher motivation to teach together on the quality of learning in junior high schools in the Lamaknen district, East Nusa Tenggara. (2) There is a positive and significant influence of the Principal's leadership on the quality of learning in junior high schools in the Lamaknen district, East Nusa Tenggara. (3) There is a positive and significant influence of teacher competence on the quality of the learning process in junior high schools in Lamaknen sub-district, East Nusa Tenggara. (4) There is a positive and significant influence of the teaching motivation of teachers on the quality of learning in junior high schools in Lamaknen District, East Nusa Tenggara.